The uncommon approaches of teaching the programming courses: the perspective of experienced lecturers / Jamal Othman and Naemah Abdul Wahab - Othman, Jamal; Abdul Wahab, Naemah (UiTM Cawangan Perlis, 2016)
Programming courses have become one of the important courses for all sciences programs which are offered at the tertiary level (university). Currently, the students are compulsory to enroll in at least one basic programming course in order to fulfill the requirement of the university. The university needs more experienced lecturers to teach the programming courses. Most of the students are not interested in programming subject and they have considered the programming course as a high failure rate course. As a lecturer, we should be able to change their negative perception and motivate the students to use and apply the programming skills in their life.